KECERDASAN HOLISTIK DAN KINERJA TENAGA PENJUAL ASURANSI PADA AGENSI PRUSAMURAI DENPASAR - I Gusti Ayu Wiratni Adriyani (Jurnal Manajemen dan Bisnis, 2014)
Successful achievement of an enterprise, all systems must be able to worksynergistically. Selection and coaching salespeople performed by salespeople themselvesagainst 'line' down on it, then the activity is dependent upon the salesperson's own salespeople.Various attempts have been made in the hope of salesperson performance increases, which inturn can increase agency revenue, but revenue and salesperson activity still has not shown anincrease as expected, then it should be factors in self salesperson who causes a decrease inperformance. Insurance Salesperson in carrying out his duties always have to face the otherperson; whether it be leadership, prospective clients, customers and / or fellow competitorsInsurance Salesperson.Samples in this research is about 147 person all of contract salesperson ofPRUSamurai Denpasar. The method of data collection was using the questionnaire. Dataanalysis was a statistical method of Structural Equation Modeling (SEM) and then the dataprocessed with SPSS 16.0 and AMOS 16.0 program facilities. SPSS program used to input thedata which already obtained from the data collection, while AMOS program used to displaythe result of research which related between the variables.Data analysis conducted by using SEM software AMOS through 16.0. Through datanormality test, Confirmatory Factor Analysis (CFA) test and the analysis of the influencethrough SEM. SEM analysis results indicated that the influence of the physical intelligence (X1)against the performance of salesperson (Y) that there was a positive influence of 0,138; theinfluence of intellectual intelligence (X2) against the performance of salesperson (Y) that therewas a positive influence of 0,347; the influence of emotional intelligence (X3) against theperformance of salesperson (Y) that there was a positive influence of 0,307; spiritualintelligence and influence (X4) against the performance of salesperson (Y) that there was apositive influence of 0,140. It could be seen, the most dominant variable influenced salespersonperformance (Y) was the intellectual intelligence variables (X2) of 0,347.